Transmission loss and load flow allocations via genetic algorithm technique - Mohd Herwan, Sulaiman; Mustafa, M. W.; Aliman, O. (Institute of Electrical and Electronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/